2001
DOI: 10.1105/tpc.010001
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast Gene ycf9 Encodes a Photosystem II (PSII) Core Subunit, PsbZ, That Participates in PSII Supramolecular Architecture

Abstract: We have characterized the biochemical nature and the function of PsbZ, the protein product of a ubiquitous open reading frame, which is known as ycf9 in Chlamydomonas and ORF 62 in tobacco, that is present in chloroplast and cyanobacterial genomes. After raising specific antibodies to PsbZ from Chlamydomonas and tobacco, we demonstrated that it is a bona fide photosystem II (PSII) subunit. PsbZ copurifies with PSII cores in Chlamydomonas as well as in tobacco. Accordingly, PSII mutants from Chlamydomonas and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 88 publications
4
36
0
1
Order By: Relevance
“…Fluorescence analyses on intact leaves were performed using a home-made digital video imaging system. Maximal fluorescence (F m ) was measured on dark-adapted leaves with a homemade video-imaging apparatus previously described [22]…”
Section: Fluorescence Analysismentioning
confidence: 99%
“…Fluorescence analyses on intact leaves were performed using a home-made digital video imaging system. Maximal fluorescence (F m ) was measured on dark-adapted leaves with a homemade video-imaging apparatus previously described [22]…”
Section: Fluorescence Analysismentioning
confidence: 99%
“…In cyanobacteria, this complex consists of 17 membrane-spanning subunits, three extrinsic proteins, and more than 70 cofactors including chlorophylls (Chls), carotenoids, plastoquinones, pheophytins, manganese atoms, non-heme iron, calcium, chlorides, and heme groups, with a total molecular weight of around 350 kDa for a monomer. Among the 17 trans-membrane subunits, 13 have molecular weight lower than 10 kDa, and are termed low molecular weight (LMW) subunits. Twelve LMW subunits have single trans-membrane helix, and only PsbZ has two trans-membrane helices.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is significant support for the specific role of the PSII subunit, PsbS, in regulating NPQ in terrestrial plants (Niyogi et al 2005). Swiatek et al (2001) reported that another photosystem subunit, PsbZ, regulates NPQ in C. reinhardtii. Thus, the precise molecular role of PsbS in regulating NPQ remains equivocal.…”
mentioning
confidence: 99%